Analisis Eksternalitas Industri Pariwisata Pantai Batu Pinagut Terhadap Pelaku Ekonomi dan Masyarakat - Rita Olii; herwin mopangga; frahmawati bumulo (Economic Reviews Journal, 2024)
The progress of the management of the tourism sector, especially Batu Pinagut Beach, will have a direct impact on the community through aspects such as Economic, Social and environmental. Externalities can be in the form of positive/negative impacts on the surrounding community, the impact of externalities can cause various changes in the welfare of the surrounding community. The research using a descriptive-comparative method was carried out to compare a condition before and after the existence of the Batu Pinagut Beach tourist attraction located in East Boroko Village, Kaidipang District, North Bolaang Mongondow Regency, North Sulawesi Province. Data collection techniques with questionnaires and direct interviews with the community around Batu Pinagut Beach. The externality data analysis method used uses a different test from the Wilcoxon Signed Rank Test. The results showed that there were differences between before and after the tourist attraction was managed, there were positive externalities in the economic and social aspects, while negative externalities in the environmental aspects in the Batu Pinagut beach tourist attraction.